Applications of Computing and Communication Technologies: First International Conference, ICACCT 2018, Delhi, India, March 9, 2018, Revised Selected Papers - Deka, Ganesh Chandra; Kaiwartya, Omprakash; Vashisth, Pooja; Rathee, Priyanka (Communications in computer and information science, 2018)
This book (CCIS 899) constitutes the refereed proceedings of the First International Conference on Applications of Computing and Communication Technologies, ICACCT 2018, held in Delhi, India, in March 2018. The 30 full papers were carefully reviewed and selected from 109 submissions. The papers are organized in topical sections on communication and system technologies, computing and network technologies, application and services.